Amelioration of Chromium-Induced Oxidative Stress by Combined Treatment of Selected Plant-Growth-Promoting Rhizobacteria and Earthworms via Modulating the Expression of Genes Related to Reactive Oxygen Species Metabolism in Brassica juncea - Sharma, Pooja; Chouhan, Rekha; Bakshi, Palak; Gandhi, Sumit G.; Kaur, Rupinder; Sharma, Ashutosh; Bhardwaj, Renu (Frontiers in Microbiology, 2022)
Chromium (Cr) toxicity leads to the enhanced production of reactive oxygen species (ROS) which are extremely toxic to the plant and must be minimized to protect the plant from oxidative stress. The present study was carried out to investigate the effect of PGPR (Pseudomonas aeruginosa and Burkholderia gladioli) and earthworms (Eisenia fetida) on the antioxidative defense system in Brassica juncea seedlings under Cr stress. The Cr toxicity reduced the fresh weight and dry weight of seedlings, enhanced the levels of superoxide anion (O2•‾), hydrogen peroxide (H2O2), malondialdehyde (MDA), electrolyte leakage (EL), which lead to membrane as well as the nuclear damage and reduced cellular viability in B. juncea seedlings. The activities of the antioxidant enzymes, viz. superoxide dismutase (SOD), guaiacol peroxidase (POD), ascorbate peroxidase (APOX), glutathione peroxidase (GPOX), dehydroascorbate reductase (DHAR) and glutathione reductase (GR) were increased, however, a reduction was observed in the activity of catalase (CAT) in the seedlings under Cr stress. Inoculation of the PGPRs and the addition of the earthworms enhanced the activities of all other antioxidative enzymes except GPOX, in which a reduction of the activity was observed. The total lipid soluble and water-soluble antioxidants and the non-enzymatic antioxidants, viz. ascorbic acid and glutathione, an enhance accumulation was observed upon the inoculation with PGPR and earthworms. The supplementation of PGPR with earthworms (combined treatment) reduced both the ROS and the MDA content by modulating the defense system of the plant. The histo-chemical studies also corroborated that the combined application of PGPR and earthworms reduced O2•‾, H2O2, lipid peroxidation, reduced membrane and nuclear damage and improved cell viability. The expression of key antioxidant enzyme genes viz., SOD, CAT, POD, APOX, GR, DHAR and GST showed the upregulation of these genes at post-transcriptional level upon the combined treatment of the PGPR and earthworms, thereby corresponding to the improved plant biomass. However, a reduced expression of RBOH1 gene was noticed in seedlings supplemented under the effect of PGPR and earthworms grown under Cr stress. The results provided the sufficient evidence regarding the role of PGPR and earthworms in amelioration of Cr-induced oxidative stress in B. juncea.